2023
DOI: 10.1101/2023.07.13.548808
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The substrate-binding domains of the osmoregulatory ABC importer OpuA transiently interact

Marco van den Noort,
Panagiotis Drougkas,
Cristina Paulino
et al.

Abstract: Bacteria utilize various strategies to prevent internal dehydration during hypertonic stress. A common approach to countering the effects of the stress is to import compatible solutes such as glycine betaine, leading to simultaneous passive water fluxes following the osmotic gradient. OpuA from Lactococcus lactis is a type I ABC-importer that uses two substrate-binding domains (SBDs) to capture extracellular glycine betaine and deliver the substrate to the transmembrane domains for subsequent transport. OpuA s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 70 publications
2
7
0
Order By: Relevance
“…The force required to break this interaction was higher at low salt (buffer only) than in the presence of buffer plus 600 mM KCl. This increase in force matches the observation of a larger high FRET population in the low salt condition from smFRET data 28 . Additionally, the experimental values for the change in length 11 ± 5 nm and 15 ± 6 nm in buffer without and with salt, respectively, are in the same order of magnitude as expected from an interaction ( Materials and Methods, Figure 6 ).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The force required to break this interaction was higher at low salt (buffer only) than in the presence of buffer plus 600 mM KCl. This increase in force matches the observation of a larger high FRET population in the low salt condition from smFRET data 28 . Additionally, the experimental values for the change in length 11 ± 5 nm and 15 ± 6 nm in buffer without and with salt, respectively, are in the same order of magnitude as expected from an interaction ( Materials and Methods, Figure 6 ).…”
Section: Discussionsupporting
confidence: 86%
“…OpuA-K521C has been purified and reconstituted in MSP1E3D1 lipid nanodiscs formed from a synthetic lipid mixture consisting of a weight ratio of 38:12:50 DOPE:DOPG:DOPC. It has previously been shown that the salt-, glycine betaine-, ATP- and c-di-AMP-dependent ATPase activities of the mutant are similar to those of the wild-type 28 .…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations